Global supply chain security and management : appraising programs, preventing crimes - Prokop, Darren (Butterworth-Heinemann is an imprint of Elsevier, 2017)
Global Supply Chain Security and Management: Appraising Programs, Preventing Crimes examines the relationship between securing a supply chain and promoting more efficient worldwide trade. Historically, the primary goal of supply chain security was guarding against theft and damage. Today, supply chains are also on the frontlines in the fight against terrorism. This book showcases industry leaders and their best practices, also exploring how the government is both a policing organization and a supply chain partner. In addition, it covers the critical roles that various technologies play, focusing on how Big Data is collected and turned into knowledge. By using the tools provided, readers will gain a stronger understanding of the challenges and opportunities faced by any organization that imports or exports products. Outlines the latest technologies being used to secure infrastructures Leverages game theory to express the strategic interactions of government and business Covers the latest U.S. regulations and provides analytical tools to help make sense of these regulations Incorporates the latest theories and techniques of industrial organization, economics, and security.